Three dimensional printed polylactic acid-hydroxyapatite composite scaffolds for prefabricating vascularized tissue engineered bone: An in vivo bioreactor model. Issue 1 (December 2017) - Zhang, Haifeng; Mao, Xiyuan; Zhao, Danyang; Jiang, Wenbo; Du, Zijing; Li, Qingfeng; Jiang, Chaohua; Han, Dong
Abstract The repair of large bone defects with complex geometries remains a major clinical challenge. Here, we explored the feasibility of fabricating polylactic acid-hydroxyapatite (PLA-HA) composite scaffolds. These scaffolds were constructed from vascularized tissue engineered bone using anin vivo bioreactor (IVB) strategy with three-dimensional printing technology. Specifically, a rabbit model was established to prefabricate vascularized tissue engineered bone in two groups. An experimental group (EG) was designed using a tibial periosteum capsule filled with 3D printed (3DP) PLA-HA composite scaffolds seeded with bone marrow stromal cells (BMSCs) and crossed with a vascular bundle. 3DP PLA-HA scaffolds were also combined with autologous BMSCs and transplanted to tibial periosteum without blood vessel as a control group (CG). After four and eight weeks, neovascularisation and bone tissues were analysed by studying related genes, micro-computed tomography (Micro-CT) and histological examinations between groups. The results showed that our method capably generated vascularized tissue engineered bonein vivo . Furthermore, we observed significant differences in neovascular and new viable bone formation in the two groups. In this study, we demonstrated the feasibility of generating large vascularized bone tissuesin vivo with 3DP PLA-HA composite scaffolds.